The Relationship between Watching Mukbang Video with Dietary Behavior and Nutrition Status in Teens - Zahirah, Najha Ayis; Safitri, Septiana; Madiha, Siti Nur Zahrina; Andyarini, Esti Novi (International Conference on Sustainable Health Promotion, 2023)
The trend of the mukbang has a distinct attraction for those who watch it and thus encourage one to eat. It has a positive and negative impact on dietary behavior and nutritional status, including teens those of more frequently watching mukbang videos. This study is to learn the relationship between watching video mukbang and dietary behavior and nutrition status in teens. The method done in this study is the literature review of critical assessments previously published. Articles from the two databases of Pubmed and Science Direct. The ten articles were analyzed and synthesized based on screening, selection, and selection of articles. Studies show that watching habits can encourage unhealthy eating practices and potentially addictive use of technology that can result in teens gaining weight commonly known as obesity. However, this habit also has a positive impact related to increasing the appetite of teenagers. Based on the results of the literature, it can be concluded that there is a relationship between the habit of watching mukbang video with dietary behavior and nutrition status in teens. That habit has both positive and negative impacts, but the negative impact is more